MENINGKATKAN KESADARAN MASYARAKAT AKAN PENTINGNYA PEMENUHAN GIZI DALAM MENCEGAH STUNTING DI DESA SUKAMAJU KECAMATAN LABUAN KABUPATEN PANDEGLANG - Hamer, Welliam; Bryan Maliki, Billy; Mapruhah, Aap (CV. Era Digital Nusantara, 2022)
Stunting is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the standard age. In addition to nutritional factors, stunting is caused by a lack of public knowledge, especially mothers who have infants and toddlers about stunting. The stunting control model is through increasing family empowerment related to the prevention of infectious diseases, utilizing the yard as a source of family nutrition and improving environmental sanitation. Implementation of education carried out by Untirta students in Group 96 of Kuliah Kerja Mahasiswa (KKM) in Sukamaju Village, Labuan District, Pandeglang Regency through socialization about stunting prevention. Some of the activities consist of main programs and supporting programs that focus on health, education, entrepreneurship, and the environment. The result is the implementation of a work program by creating creative content that can increase public awareness. In addition, the implementation of KKM in Sukamaju Village received a very positive response from the community. Keywords: Comunity Awareness, Nutrition Fulfilment, Stunting